2016
DOI: 10.1177/1457496916654097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Morbidity and Mortality in Esophageal Perforation: Retrospective Study of 80 Patients

Abstract: Intraluminal perforations, rapid initiation of therapy, and non-operative treatment were associated with favorable outcomes. The perforation site did not have an impact on outcomes. Esophageal resection was associated with high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…[11][12][13] The rate of iatrogenic injury is increased with endoscopic examinations, placement of tubes, stent application, submucosal dissection, and endomucosal resection and up to 60% in the most recent series. [1] Furthermore, there is substantial heterogeneity in the etiologies of perforation including Boerhaave syndrome, tumor perforation, thoracic trauma, swallowing foreign bodies, and acid or caustic substances. [14][15][16] In our study, the rate of iatrogenic perforation was 53.8% and spontaneous perforation was 38.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] The rate of iatrogenic injury is increased with endoscopic examinations, placement of tubes, stent application, submucosal dissection, and endomucosal resection and up to 60% in the most recent series. [1] Furthermore, there is substantial heterogeneity in the etiologies of perforation including Boerhaave syndrome, tumor perforation, thoracic trauma, swallowing foreign bodies, and acid or caustic substances. [14][15][16] In our study, the rate of iatrogenic perforation was 53.8% and spontaneous perforation was 38.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptoms of EP are thoracic pain (58%), dyspnea (30%), dysphagia (24%), vomiting and nausea (21%), coughing (9%), and hypovolemic shock (11%). [1] Malignancy is the most frequently identified underlying pathology. CT is the most commonly used diagnostic tool in all perforation etiologies.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…heterogeneity in the patient populations and therapeutic management [51, 95 -100]. Nonsurgical management seemed to be related to a lower rate of morbidity [51,95]. A 12-year English multicenter retrospective study including 2564 patients with esophageal perforation (152 cases with iatrogenic perforation) revealed that high hospital case volume was associated with significant reductions in 30-day mortality (OR 0.68, P = 0.001) and 90-day mortality (OR 0.69, P = 0.001) [101].…”
Section: Treatment: Esophagusmentioning
confidence: 99%
“…In adults endoscopy with stent placement has been advocated as a minimally invasive procedure to preserve the patient's esophagus [8,11,15,22,26,28]. Most recently, the use of fully covered self-expandable metal stents (SEMSs) has been reported with different outcome for benign esophageal disorders in children [2,4,7,17,19,24].…”
Section: Introductionmentioning
confidence: 99%